WACANA HUMOR PADA TAGAR #MATANAJWAMENANTITERAWAN DI TWITTER - Novrita Widiyastuti (Jurnal Pustaka Komunikasi, 2021)
Mata Najwa, a talk show hosted by Najwa Shihab, on September 29, 2020 uploaded unusual video which questioning the existence of Terawan Agus Putranto, The Minister of Health Republic Indonesia at that time, whom never appears in the media to make statement about Government’s treatment of pandemic Covid-19. Mata Najwa tried to attract public’s attention by uploading a video that using empty chair interview technique, pretends Terawan was shows up in the middle of the show. Until the video with hastag #MataNajwaMenantiTerawan became trending topic in Twitter and created new humor discourses from netizens. The humor discourses in this hashtag is interested to be researched, that makes the objective of this research is to discover humor discourses contained in the video #MataNajwaMenantiTerawan, as well as user’s tweets that created new humor discourses in Twitter. Concept framework of this research is concepts about satire, parody, parikena, dan sarcasm. Research method: constructivism paradigm with qualitative type of research. Data collection methods: observing video Mata Najwa duration 4 minutes 22 seconds, timeline on Twitter with hashtag #MataNajwaMenantiTerawan, interview with Executive Producer of Mata Najwa from Narasi TV and documentation from various sources.